Answer:
-4 and -3
Step-by-step explanation:
You can evaluate the function at the middle of the range of interest, which is [-6, -2], and see which side of that the root lies on.
f(-4) = ((-(-4) -2)(-4) +5)(-4) -6 = (2(-4) +5)(-4) -6 = (-3)(-4) -6 = 6
Since f(0) = -6, the root lies between -4 and 0. The x-value of -3 further divides the interval [-4, -2] in half, so we can try ...
f(-3) = ((-(-3) -2)(-3) +5)(-3) -6 = (1(-3) +5)(-3) -6 = 2(-3) -6 = -12
The interval [-4, -3] brackets the root.
_____
We have written the polynomial in "Horner form" to make evaluation easier.
f(x) = ((-x -2)x +5)x -6